Identificación de los estilos de aprendizaje de los estudiantes universitarios: revisión de literatura - Cárdenas Palomino, Franz Ramiro (2021)
The learning style is the unique trait that defines the way of learning of each individual, they are not unique in a person. Thus, it is important that university teachers know the learning styles of their students and, based on this, plan improved strategies, change methodologies, among others. Objective. Identify how the learning styles of university students have been identified and if they have beenrelated to any variable. Materials and methods. It is a systematic bibliographic research study, with a descriptive approach. The analysis was carried out in databases of Scielo, Dialnet and Google Academic. Results. A final sample of 24 articles was obtained, which evidenced the identification of various questionnaires used to identify learning styles in university students and their correlations in greater quantity with academic performance. Conclusions. The analyzed studies provided a vision about the importance of learning styles, which should serve as the basis for future research, given that there is still a knowledge gap in various careers and academic cycles; in addition to its correlation with others not mentioned in this research